Basis for the model of parameter permeability prediction of productive strata in oil and gas deposits development; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 3 - Peshkov V. Е.; Solyanik А. S.; Krylov О. V.; Zakharova А. А.; Tikhomirova N. О. (Earth science, 2007)
Заглавие с титульного листа